Introdução ao debate sobre a metropolização - Guy Di Méo (Confins)
Metropolization is a universal phenomenon characterized by the concentration of a growing number of inhabitants in fluid and open urban areas. Those inhabitants live to the rhythm of unceasing mobilities and use ICTs. Their activities are more and more devoted to the production of services. One of the main original aspects of the metropolises they live in is their interconnection within a global network. Metropolization is both a very efficient global productive system and a new process of space development/occupancy. It also provides a tool that can be used in order to classify social groups within more and more fragmented spaces. This introduction stresses the main questions linked to the process of metropolization and to the social and spatial innovation forms it generates in the sciences of geographical space. Traduction of « Introduction au débat sur la métropolisation », published on the  site Hal-Shshttp://halshs.archives-ouvertes.fr/halshs-00281654/fr/